Persistent Infection by Wolbachia wAlbB Has No Effect on Composition of the Gut Microbiota in Adult Female Anopheles stephensi - Chen, Shicheng; Zhao, Jiangchao; Joshi, Deepak; Xi, Zhiyong; Norman, Beth; Walker, Edward D. (Frontiers in Microbiology, 2016)
The bacteria in the midgut of Anopheles stephensi adult females from laboratory colonies were studied by sequencing the V4 region of 16S rRNA genes, with respect to three experimental factors: stable or cured Wolbachia infection; sugar or blood diet; and age. Proteobacteria and Bacteroidetes dominated the community (> 90% of OTUs); most taxa were in the classes Flavobacteriia, Gammaproteobacteria, and Alphaproteobacteria, and were assigned to Elizabethkingia (46.9%), Asaia (6.4%) and Pseudomonas (6.0%), or unclassified Enterobacteriaceae (37.2%). Bacterial communities were similar between Wolbachia-cured and Wolbachia-infected mosquito lines, indicating that the gut microbiota were not dysregulated in the presence of Wolbachia. The proportion of Enterobacteriaceae was higher in mosquitoes fed a blood meal compared to those provided a sugar meal. Collectively, the bacterial community had a similar structure in older Wolbachia-infected mosquitoes 8 days after the blood meal, as in younger Wolbachia-infected mosquitoes before a blood meal, except that older mosquitoes had a higher proportion of Enterobacteriaceae and lower proportion of Elizabethkingia. Consistent presence of certain predominant bacteria (Elizabethkingia, Asaia, Pseudomonas and Enterobacteriaceae) suggests they would be useful for paratransgenesis to control malaria infection, particularly when coupled to a Wolbachia-based intervention strategy.